Gamification as a Strategy to Improve Sales Marketing Performance with Work Motivation as a Mediating Variable - Anisah Anisah (Dinasti International Journal of Digital Business Management, 2026)
The increasing intensity of competition in the financing industry requires companies to implement innovative human resource management strategies to sustain employee performance. This study investigates the effect of gamification on sales marketing performance, with work motivation acting as a mediating variable. A quantitative approach was employed by collecting survey data from 132 sales marketing employees of PT Adira Dinamika Multi Finance Tbk, Jambi Branch, using a census technique. The data were analyzed using Structural Equation Modeling (SEM) with AMOS software. The results indicate that gamification does not have a significant direct effect on employee performance. However, gamification has a positive and significant effect on work motivation, which in turn significantly influences sales marketing performance. Furthermore, work motivation is proven to fully mediate the relationship between gamification and employee performance. These findings suggest that the effectiveness of gamification initiatives in sales-oriented organizations depends on their ability to enhance employees’ motivational states rather than serving as a direct performance driver. This study provides empirical insights for managers in designing motivation-based gamification systems to improve sustainable sales performance in the financing industry